Maximizing wheeling performance! Wheelchair training: What is the ideal strategy and programme? - Goosey-Tolfrey, V. L. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Although the locomotion for daily wheelchair ambulation and sports involves a repetitive cyclic movement pattern which may be considered similar to that of cycling, running, or swimming, the training principles are not directly transferrable. The wheelchair athlete uses a considerably smaller amount of muscle mass which is dependent upon their disability and/or functional capacity. Generally the higher the spinal cord injury (SCI) the greater the functional impairment. For wheelchair athletes, who regularly take part in competitive sports this intriguing complex model continues with noticeable hypertrophy in the upper extremities and muscle atrophy below the level of the lesion. The main issue for the coach is with the scheduling of recovery sessions and with the selection of the most suitable tools to monitor the volume of training, as repetitive upper-limb movements are associated with shoulder complaints and degeneration. That said, regardless of disability, from a physical foundation, it is imperative to develop and/or maintain the components of fitness, and there is strong evidence to suggest that wheelchair athletes gain similar training adaptations to the able-bodied (AB) through aerobic and anaerobic conditioning. In order to develop and implement safe and effective training programmes an understanding of the nature and onset of the physical disability and indeed the exercise modality is essential. This presentation will focus on the wheelchair athlete to illustrate the differences and similarities between Olympic and Paralympic sports knowledge via four key areas; i) describe a selection of the key training modalities available to the wheelchair athlete; ii) discuss how the training prescription for the AB may be challenged in terms of its use for wheelchair athletes; iii) discuss how the tools for quantifying training load can be applied; and iv) conclude with whether an ideal upper extremity training strategy actually exists for wheelchair athletes. The presentation will provide examples of the most common training modes for the wheelchair athlete (i.e., arm crank ergometry, hand-cycling, over-ground and/or ergometer based wheelchair propulsion). I will discuss how going back to basics for exercise prescription (using RPE) may be just as effective as using sophisticated technological measures such as power meters. The presentation aims to address to a broad audience interested in wheelchair propulsion in general but especially in Paralympic sports.